2019
DOI: 10.1038/s41598-019-54642-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological performance of glyphosate and imazamox mixtures on Amaranthus palmeri sensitive and resistant to glyphosate

Abstract: The herbicides glyphosate and imazamox inhibit the biosynthetic pathway of aromatic amino acids (AAA) and branched-chain amino acids (BCAA), respectively. Both herbicides share several physiological effects in the processes triggered in plants after herbicide application that kills the plant, and mixtures of both herbicides are being used. The aim of this study was to evaluate the physiological effects in the mixture of glyphosate and imazamox in glyphosate-sensitive (GS) and -resistant (GR) populations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
5
13
0
1
Order By: Relevance
“…The DAHPS content was not affected by the herbicide in any of the populations ( Figure 5 A), which conforms to reports of the same effect in other ALS-inhibitors in Amaranthus palmeri leaves [ 45 ]. On the contrary, previous studies have shown induction of the secondary metabolism after treatment with ALS-inhibitors, which is related to an induction of the first enzyme of the shikimate pathway in pea roots [ 48 ].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The DAHPS content was not affected by the herbicide in any of the populations ( Figure 5 A), which conforms to reports of the same effect in other ALS-inhibitors in Amaranthus palmeri leaves [ 45 ]. On the contrary, previous studies have shown induction of the secondary metabolism after treatment with ALS-inhibitors, which is related to an induction of the first enzyme of the shikimate pathway in pea roots [ 48 ].…”
Section: Resultssupporting
confidence: 90%
“…On the contrary, previous studies have shown induction of the secondary metabolism after treatment with ALS-inhibitors, which is related to an induction of the first enzyme of the shikimate pathway in pea roots [ 48 ]. Similarly, the sulfonylurea application did not induce quinate accumulation or AAA accumulation, as reported after other ALS-inhibitors [ 7 , 45 ]. The lack of detection of these typical physiological effects on the secondary metabolism after ALS-inhibition suggests that the study did not continue long enough to induce them.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Carbohydrates were accumulated in the roots as a consequence of ALS inhibition (Figure 4) as has been described before [8][9][10][11]14,32,33]. The accumulation in roots was due to a lack of use of available sugars because growth was arrested (Figure 3).…”
Section: Discussionmentioning
confidence: 56%
“…The effects on free amino acid profile were studied in the No-Hypoxia and Hypoxia-24h groups ( Figure 5) by monitoring five physiological parameters previously described to be affected by ALS inhibitors: free amino acid content, BCAA, aromatic, acidic, and amide amino acid contents [6,10,14,27]. As ALS -inhibitors cause a general increase in the content of free amino acids that could mask the specific changes in each absolute content [27,28], BCAA, aromatic, acidic and amide amino acids are shown as their relative content in terms of percentage of total amino acid content ( Figure 5).…”
Section: Free Amino Acid Profilementioning
confidence: 99%